SEXUAL HARASSEMENT ANAK: UPAYA PENANGGULANGAN TINDAK PELECEHAN SEKSUAL YANG TERNORMALISASIKAN DI INDONESIA - Galih Bagas Soesilo; Mutia Febiana, Pijar Agni Winengku Alam Murtanto, Viona Erwiyanto Putri (PROSIDING, 2022)
Sexual violence that occurs in children is a problem that has not been over. The various forms of sexual violence that have been listed and regulated by law have not been fully understood by the Indonesian people. This problem is further exacerbated by the lack of understanding of how normal activity limits or even has led to forms of sexual violence. Therefore, this article was compiled to educate the general public, especially parents, community members, and law enforcers about children's rights and maximum protection efforts from various forms of sexual crimes. The method used in this discussion is a normative juridical approach. The result of the discussion is that the normalization rate of sexual abuse against children is still high in Indonesia because they still see victims as part of the cause of sexual violence and there is a rape culture mindset. This can be overcome with firm regulations and efforts to still provide an understanding of the boundaries of what sexual harassment is and also to normalize this behavior. So that a need for an active role from various parties in carrying out preventive and repressive efforts to understand and eradicate sexual violence against children. Keywords : Child, Normalization, Sexual Violence